2015
DOI: 10.1371/journal.pone.0120666
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Harvest on the Sustainability and Leaf Productivity of Populations of Two Palm Species in Maya Homegardens

Abstract: Traditional management practices are usually thought to be sustainable. The Maya manage Sabal (Arecaceae) palms in homegardens, using their leaves for thatching. The sustainability of such production systems depends on the long-term persistence of palm populations, whereas resource availability also depends on the number of leaves on individual palms. We examined how leaf harvest affects Sabal yapa and S. mexicana population growth rates (λ) and leaf production, comparing traditional and alternative harvest re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…In general, previous studies have shown that many palm species are resilient to defoliation [ 9 , 10 ]. However, effects vary among species, and depend on the intensity and frequency of leaf removal [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, previous studies have shown that many palm species are resilient to defoliation [ 9 , 10 ]. However, effects vary among species, and depend on the intensity and frequency of leaf removal [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because leaves from a wide range of palm species are economically and/or culturally important, a number of studies have explored the effects of harvest on individuals [ 9 , 10 ], [ 14 ]. Studies have been carried out on species found in both wet and dry tropical and subtropical ecosystems, including species such as Brahea dulcis , Sabal mexicana , S .…”
Section: Introductionmentioning
confidence: 99%
“…Effects on soil and hydric dynamics in palm groves that are still poorly known need to be assessed. Despite the relevance of Soyate, a further assessment of other palm species in Mexico is needed, such as for the Sabal species which represents an important resource in the warm and humid regions of southeastern Mexico [29,39,40].…”
Section: Traditional Management: Insights For Sustainabilitymentioning
confidence: 99%
“…Similarly, as in other countries of South America [23], palms in Mexico have mostly been used as material for construction, food, and the production of tools and utensils of domestic and agricultural use. The palm's leaves, fruits, and apical meristems are the most used parts [21,29,[36][37][38][39][40]. The plant fiber which makes up the leaves is of primary importance in roof thatching and the production of household goods [29,41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation